Solution-processed single crystal microsheets of a novel dimeric phthalocyanine-involved triple-decker for high-performance ambipolar organic field effect transistors. Issue 95 (13th November 2017) - Lu, Guang; Kong, Xia; Sun, Junshan; Zhang, Liangliang; Chen, Yanli; Jiang, Jianzhuang
Abstract : Single-crystal microsheets of a novel dimeric phthalocyanine are successfully obtained via a facile solution process with excellent carrier mobilities of 18 cm 2 V −1 s −1 for hole and 0.3 cm 2 V −1 s −1 for electron, respectively. Abstract : Well-defined single crystal microsheets of a novel dimeric phthalocyanine involved sandwich-type triple-decker complex [Pc(SC6 H13 )8 ]2 Eu2 [BiPc(SC6 H13 )12 ]Eu2 [Pc(SC6 H13 )8 ]2 (1 ) are successfully prepared via a facile solution process. High-performance single crystal OFETs with a hole mobility of 18 cm 2 V −1 s −1 and an electron mobility of 0.3 cm 2 V −1 s −1 are obtained.